0286 Schedule Characteristics of Heavy Vehicle Drivers are Associated with Eye-Blink Indicators of Real-Time Drowsiness on the Road. (27th May 2020) - Shekari Soleimanloo, S; Sletten, T L; Clark, A; Cori, J M; Wolkow, A P; Beatty, C; Shiferaw, B; Barnes, M; Tucker, A J; Anderson, C; Rajaratnam, S M; Howard, M E
Abstract: Introduction: While up to 52% of heavy vehicle crashes are drowsiness-related, the contributions of schedule factors to real-time objective drowsiness in heavy vehicle drivers (HVDs) have not been studied. Eye-blink parameters are a reliable indicator of driver drowsiness. This study aimed to examine the relationship between work-related factors and objective drowsiness in HVDs. Methods: HVDs (all males, aged 49.5 ± 8 years) undertook 5- weeks of sleep-wake monitoring (Philips Actiwatch, N=15), and 4-weeks of infrared oculography (Optalert, Melbourne, Australia) to monitor their eye-blink parameters (averaged each minute) while driving their own vehicle (N=12). Participants slept for 5.75± 1.4 hours before the drives. Drowsiness events were defined as any Johns Drowsiness Scores (JDS) scores larger than 2.6 based on prior research. The relationships of schedule factors and drowsiness events per hour were assessed via mixed linear regression models. Results: Drowsiness event rates were 3–5 times greater between 22:00 and 03:00 hours compared to between 16:00 and 17:00 hours (17- 25 events/h vs 5 events/h, P= 0.0001 to 0.007). The frequency of drowsiness events at night varied with shift start time and time into shift (P= 0.0001 to 0.001). Compared to the first hour of driving, drowsiness event rates rose significantly during the 13 th to the 21 st hours into the shift (13- 59 events/h vs 5.5 events/h, P= 0.0001 to 0.007). During sequential night shifts drowsiness events were 1.8 times more common compared to 1–3 sequential day shifts (9 events/h vs 5 events/h, P= 0.012 to 0.019). Conclusion: Driving at night, for more than 12 hours and sequential night shifts increase real-time drowsiness in HVDs, with these factors interacting resulting in even higher rates of drowsiness events. Longitudinal studies in larger populations will further define how these factors interact to inform the work scheduling of HVDs to reduce the risk of drowsiness. Support: This research was supported by the CRC for Alertness, Safety and Productivity.